2020
DOI: 10.3390/plants9121808
|View full text |Cite
|
Sign up to set email alerts
|

Identification of BELL Transcription Factors Involved in Nodule Initiation and Development in the Legumes Pisum sativum and Medicago truncatula

Abstract: Single three-amino acid loop extension (TALE) homeodomain proteins, including the KNOTTED-like (KNOX) and BEL-like (BELL) families in plants, usually work as heterodimeric transcription factor complexes to regulate different developmental processes, often via effects on phytohormonal pathways. Nitrogen-fixing nodule formation in legumes is regulated by different families of homeodomain transcription factors. Whereas the role of KNOX transcription factors in the control of symbiosis was studied early, BELL tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…In pea, GAs reduce the number of nodules, but increase their growth in a way independent of ethylene, a key growth regulator of nodulation [185]. In Pisum sativum and Medicago truncatula, DELLA proteins regulate nodule formation by modulating the activities of KNOX and BEL1-LIKE HOMEODOMAIN (BELL) TFs [186,187]. In roots, DELLA proteins, in conjunction with other GRAS proteins, are necessary for mycorrhizal colonization.…”
Section: Root Symbiosismentioning
confidence: 99%
“…In pea, GAs reduce the number of nodules, but increase their growth in a way independent of ethylene, a key growth regulator of nodulation [185]. In Pisum sativum and Medicago truncatula, DELLA proteins regulate nodule formation by modulating the activities of KNOX and BEL1-LIKE HOMEODOMAIN (BELL) TFs [186,187]. In roots, DELLA proteins, in conjunction with other GRAS proteins, are necessary for mycorrhizal colonization.…”
Section: Root Symbiosismentioning
confidence: 99%
“…Different species have been found to vary considerably with respect to the number of TALE family members they harbor. In this study, we identified a total of 18 CsTALE family genes in sweet orange, which compares with the 35 in Populus trichocarpa ( Zhao et al, 2019 ), 18 in Ananas comosus ( Ali et al, 2019 ), and 14 in Medicago truncatula ( Dolgikh et al, 2020 ), which could reflect differences in genome size and ploidy level. We established that the 18 Cs TALE proteins differ notably in terms of amino acid residues and physicochemical properties.…”
Section: Discussionmentioning
confidence: 99%
“…The homeobox gene is a transcriptional regulator that encodes the homeodomain (HD), which is widely found in eukaryotes. The typical HD consists of 60 amino acids, which can form a 3-helical domain in space [1][2][3]. However, there are some exceptions, such as the TALE (Three Amino-acid Loop Extension) gene families, which encode an atypical DNA binding domain consisting of 63 amino acids, with three additional amino acid residues (P-Y-P) inserted between the first and second helices [3].…”
Section: Introductionmentioning
confidence: 99%
“…The typical HD consists of 60 amino acids, which can form a 3-helical domain in space [1][2][3]. However, there are some exceptions, such as the TALE (Three Amino-acid Loop Extension) gene families, which encode an atypical DNA binding domain consisting of 63 amino acids, with three additional amino acid residues (P-Y-P) inserted between the first and second helices [3]. In plants, the TALE gene families include two gene subfamilies, which are known as homeodomain) and BLH, which is sometimes called BEL (BEL1-like homeodomain) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation